Human Resource Management in “Freelance Economy” for Freelance Workers in Surabaya - emma maria rompas; jajuk Suprijati (PT. Anagata Sembagi Education, 2025)
This study aims to analyze how workers in the freelance economy manage time management, skills, income uncertainty, and provide labor protection. The freelance economy offers flexibility for freelancers in determining their own work schedules, but also presents challenges in terms of income stability and labor protection. This study focuses on freelance workers in Surabaya, with research subjects including freelance photographers, website developers, and Gojek drivers. The research method used a qualitative approach with in-depth interviews with freelance workers. The information obtained was analyzed using thematic analysis to identify patterns and strategies used by freelance workers in managing challenges in their work. The results show that freelance workers implement various strategies in facing their work challenges. In terms of time management, work flexibility allows them to set their own schedules, but without good time discipline, productivity can decline. In terms of skills management, freelance workers must continuously improve their skills through online courses or professional communities to remain competitive. In the face of income uncertainty, freelance workers adopt income diversification and financial planning strategies to mitigate financial risks. In addition, the lack of labor protection is a major problem, where freelance workers do not have access to social security and health insurance, forcing them to seek protection independently. This research has implications for freelance workers, digital platforms, and the government in building a more sustainable freelance economy ecosystem. Clearer regulations are needed to improve freelance worker protection, as well as more transparent policies from digital platforms regarding incentive and rating systems.